Consumer decision-making and segmentation of dates market in Saudi Arabia - Alali, Bashaeer Mohammed; Mosbah, Ezzeddine Belgacem; Ali, Abda (Italian Journal of Food Science, 2023)
The study aimed to investigate factors influencing purchasing of dates in Saudi Arabia and its market segmentation. Principal components analysis (PCA) and clustering were used on the data obtained by interviewing a sample of 280 people. The main findings indicated two major principal components (PCs) explaining consumer behaviour: marketing accounted for 51.7% of the population’s information and gender and job determine 20.83%. Clustering provided three groups of consumers: (1) poor or unemployed women interested in the lowest price, (2 ) wealthy women interested in marketing motivation and (3) less wealthy women interested in price promotion. The study recommended a pink marketing strategy for wealthy women.